Mistletoes Play Different Roles in a Modular Host-Parasite Network - Genini, Julieta [UNESP]; Cortes, Marina C.; Guimaraes, Paulo R.; Galetti, Mauro [UNESP] (Wiley-Blackwell, 2012)
Antagonistic interactions between host plants and mistletoes often form complex networks of interacting species. Adequate characterization of network organization requires a combination of qualitative and quantitative data. Therefore, we assessed the distribution of interactions between mistletoes and hosts in the Brazilian Pantanal and characterized the network structure in relation to nestedness and modularity. Interactions were highly asymmetric, with mistletoes presenting low host specificity (i.e., weak dependence) and with hosts being highly susceptible to mistletoe-specific infections. We found a non-nested and modular pattern of interactions, wherein each mistletoe species interacted with a particular set of host species. Psittacanthus spp. infected more species and individuals and also caused a high number of infections per individual, whereas the other mistletoes showed a more specialized pattern of infection. For this reason, Psittacanthus spp. were regarded as module hubs while the other mistletoe species showed a peripheral role. We hypothesize that this pattern is primarily the result of different seed dispersal systems. Although all mistletoe species in our study are bird dispersed, the frugivorous assemblage of Psittacanthus spp. is composed of a larger suite of birds, whereas Phoradendron are mainly dispersed by Euphonia species. The larger assemblage of bird species dispersing Psittacanthus seeds may also increase the number of hosts colonized and, consequently, its dominance in the study area. Nevertheless, other restrictions on the interactions among species, such as the differential capacity of mistletoe infections, defense strategies of hosts and habitat types, can also generate or enhance the observed pattern.
Keywords: Brazilian Pantanal; coevolution; dispersal; host-mistletoe interaction network; interaction asymmetry; nestedness